2017
DOI: 10.3803/enm.2017.32.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Malignancy in Thyroid Nodules 4 cm or Larger

Abstract: BackgroundSeveral authors have questioned the accuracy of fine-needle aspiration cytology (FNAC) in large nodules. Some surgeons recommend thyroidectomy for nodules ≥4 cm even in the setting of benign FNAC, due to increased risk of malignancy and increased false negative rates in large thyroid nodules. The goal of our study was to evaluate if thyroid nodule size is associated with risk of malignancy, and to evaluate the false negative rate of FNAC for thyroid nodules ≥4 cm in our patient population.MethodsThis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
6
24
1
Order By: Relevance
“…In another study, McHenry et al have reported that the mean diameter of malignant nodules is lower than that of benign nodules (p< 0.001), and therefore, the nodule diameter could not be a predictor of malignancy (10). (20). In our study, there was no significant difference between the > 4 cm group and the < 4 cm group in terms of malignancy (p= 0.91).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In another study, McHenry et al have reported that the mean diameter of malignant nodules is lower than that of benign nodules (p< 0.001), and therefore, the nodule diameter could not be a predictor of malignancy (10). (20). In our study, there was no significant difference between the > 4 cm group and the < 4 cm group in terms of malignancy (p= 0.91).…”
Section: Discussioncontrasting
confidence: 66%
“…They have recommended not to use nodule size as a single independent factor while making the decision on thyroidectomy for ≥ 4 cm nodules (15). Megwalu et al have found false negativity rate of FNAB as 0% in their study with ≥ 4 cm nodules, and they have recommended not to perform thyroidectomy automatically in every patient with ≥ 4 cm nodule and a benign FNAB result (20). Kuru et al have found that false negative rates are 1.3% and 4.3% when they have compared < 4 cm nodules and ≥ 4 cm nodules, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The authors stated that large nodule size should not be considered as an indication for diagnostic surgery. However, Raj et al and Megwalu et al reported that the malignancy rate was not associated with the risk of malignancy in ≥40 mm nodules . Consistent with Albuja‐Cruz et al, nodule size did not affect the reliability of FNAC and lobectomy was not recommended for diagnostic purposes when evaluating large nodules.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, Albuja-Cruz et al reported that there was no significant difference between the >4 cm group and the <4 cm group in terms of malignancy (p=0.91) [15]. Moreover, Megwalu et al have studied nodules ≥4 cm and have not detected an association between nodule size and malignancy (p=0.7) [16]. In addition, Cavallo et al reported that thyroid nodule size is inversely related to malignancy risk, as larger nodules have lower malignancy rates [17].…”
Section: Discussionmentioning
confidence: 99%